The CRAFITY score emerges as a paramount prognostic indicator in hepatocellular carcinoma patients received Lenvatinib and Pembrolizumab - Wu, Weijie; Yang, Zhenyun; Zou, Hao; Long, Teng; Zhou, Zhongguo; Zhang, Yaojun; Chen, Minshan; Hu, Dandan (Frontiers in Immunology, 2024)
Background: Levels of C-reactive protein (CRP) and alpha-fetoprotein (AFP) in immunotherapy (CRAFITY) scores are associated with the prognosis of patients with hepatocellular carcinoma (HCC). This study aimed to explore the efficacy of lenvatinib and pembrolizumab (Len-P) based on the CRAFITY score.Methods: In this study, 228 patients with HCC who received Len-P in Sun Yat-sen University Cancer Center were included. CRAFITY 0 score was defined as AFP level below 100 ng/ml, CRP level below 1 mg/dl, CRAFITY 1 score was defined as AFP level at least 100 ng/ml or CRP level at least 1 mg/dl. CRAFITY 2 scores were defined as AFP levels exceeding 100 ng/ml and CRP levels exceeding 100 ng/ml. The primary outcome was overall survival (OS). The second outcome was tumor response rate.The survival time of CRAFITY 0 is significantly longer than that of CRAFITY 1 and CRAFITY 2 (p =.044). Univariate analysis showed that largest tumor size (HR = 2.149; 95% CI 1.129 -4.091; p =.02), lymph node metastasis (HR = 2.012; 95% CI 1.132-3.579; p = .017), and CRAFITY (HR = 0.372; 95% CI 0.168-0.824; p = .015) were important risk determinants of OS in all patients. The results of multivariate analysis show that CRAFITY score is an independent risk factors for OS (HR = 0.719; 95% CI 0.377-1.374; p =.048). The ORR of CRAFITY 0, 1 and 2 scores were 36.4%, 32% and 27.4%, respectively (p = .556). The ORR of intrahepatic lesions by CRAFITY 0, 1 and 2 were 37.9%, 35%, 30.6% (p= .688).CRAFITY score is a good predictor of prognosis in HCC patients receiving Len-P.